Adolescents' views on preventing self-harm: a large community study - Fortune, S; Sinclair, J; Hawton, K (Springer, 2008)
Background: Deliberate self-harm (DSH) is a major problem in young people in the United Kingdom. The majority of young people who harm themselves do not seek help and therefore community based prevention strategies are important. However little is known about young peoples' views on the prevention of DSH. The aims of this study were to identify what adolescents believe can be done to prevent them from feeling like they want to harm themselves, and to investigate differences in the views held according to gender, ethnic group and previous experiences of self-harm. Method: Pupils is a representative sample of 41 secondary schools in England completed an anonymous, self-report questionnaire including the question "what do you think could be done to help prevent young people from feeling that they want to harm themselves?" Thematic analytic methods were used to categorise responses, which were then also analysed by gender, ethnicity, lifetime history of DSH and lifetime exposure to DSH among friends. Results: The written responses of 2,954 students aged 15-16 years were analysed. Eleven broad categories of responses were identified covering causes and possible ways of preventing suicidal behaviour in young people, including: the primacy of informal social networks over professional organisations, the importance of confiding stable relationships, the need for structured group activities, and the key role that schools play in young peoples lives. Mental illness was mentioned by only 3% of respondents, although concerns about stigma acted as a barrier to seeking help for some young people. Bullying and serious problems at home were highlighted as psychosocial stressors that need to be addressed. Conclusions: The adolescents in this study considered family, friends and school as the main sources of support in preventing suicidal behaviour, and more pertinent than external helping agencies. Enhancing the provision of school-based mental health programmes and increased youth-orientation in helping services are indicated.